Worry Is Good for Breast Cancer Screening: A Study of Female Relatives from the Ontario Site of the Breast Cancer Family Registry. (28th June 2012) - Zhang, Li Rita; Chiarelli, Anna M.; Glendon, Gord; Mirea, Lucia; Knight, Julia A.; Andrulis, Irene L.; Ritvo, Paul
Abstract : Background . Few prospective studies have examined associations between breast cancer worry and screening behaviours in women with elevated breast cancer risks based on family history. Methods . This study included 901 high familial risk women, aged 23–71 years, from the Ontario site of the Breast Cancer Family Registry. Self-reported breast screening behaviours at year-one followup were compared between women at low (N = 305 ), medium (N = 433 ), and high (N = 163 ) levels of baseline breast cancer worry using logistic regression. Nonlinear relationships were assessed using likelihood ratio tests. Results . A significant non-linear inverted " U " relationship was observed between breast cancer worry and mammography screening (P = 0.034 ) for all women, where women at either low or high worry levels were less likely than those at medium to have a screening mammogram. A similar significant non-linear inverted " U " relationship was also found among all women and women at low familial risk for worry and screening clinical breast examinations (CBEs). Conclusions . Medium levels of cancer worries predicted higher rates of screening mammography and CBE among high-risk women.